2016
DOI: 10.1021/acsami.5b12652
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Effect of Vertical Graphene on the High Performance of Supercapacitor Electrode

Abstract: Graphene and its composites are widely investigated as supercapacitor electrodes due to their large specific surface area. However, the severe aggregation and disordered alignment of graphene sheets hamper the maximum utilization of its surface area. Here we report an optimized structure for supercapacitor electrode, i.e., the vertical graphene sheets, which have a vertical structure and open architecture for ion transport pathway. The effect of morphology and orientation of vertical graphene on the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 30 publications
3
66
0
1
Order By: Relevance
“…Reproduced with permission. [26] Copyright 2016, American Chemical Society. grow directly on conductive substrates, and thus the non-conductive polymeric binders that inevitably leads to the increase of electrical resistance for charge transport and the reduction of power and energy densities can be avoided.…”
Section: Electric Double-layer Capacitors (Edlcs)mentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [26] Copyright 2016, American Chemical Society. grow directly on conductive substrates, and thus the non-conductive polymeric binders that inevitably leads to the increase of electrical resistance for charge transport and the reduction of power and energy densities can be avoided.…”
Section: Electric Double-layer Capacitors (Edlcs)mentioning
confidence: 99%
“…The effects of graphene orientation and shape on the electrochemical properties of graphene-based electrodes have been investigated. [26] Figure 5d-i present the morphologies of graphene sheets with different orientations and their impact on the ion transport capability and the charge storage capacity. As compared with the horizontally packed graphene layers, VAGNA electrodes provide rich open channels for the access of electrolyte, enable the shortest straight path for ion exchange, and maximize the utilization of surface area.…”
Section: Electric Double-layer Capacitors (Edlcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…As-fabricated VArGO electrodes showed excellent volumetric (171 F cm −3 ) and areal (1.83 F cm −2 ) capacitances in 6 M KOH due to its appropriate interlayer distances and pores. Deng et al [115] adopted model calculation and experimental test to investigate the relation of electrode structure and capacitive performance with respect to the different orientation of graphene sheets. Simulation results indicated that the oriented structure and morphology of graphene sheets have strong influence on the ion transfer ability and the charge accumulation capability.…”
Section: Graphene/graphene Oxidementioning
confidence: 99%
“…In the same time, obtaining 3D graphene particles as versatile building blocks for bottom-up assembly of advanced functional materials is a very difficult problem, according to many researchers [50][51][52]. e development of cost-effective method for producing 2D and 3D graphene stacks with specified dimensions is promising for obtaining van der Waals heterostructures containing different semiconductors in the interlayer space [53,54].…”
Section: Introductionmentioning
confidence: 99%